Anaemia and adverse outcomes in European patients with atrial fibrillation: a report from the ESC-EHRA EORP atrial fibrillation general long-term registry. (3rd October 2022) - Boriani, G; Vitolo, M; Proietti, M; Malavasi, V L; Bonini, N; Romiti, G F; Imberti, J F; Fauchier, L; Nabauer, M; Potpara, T S; Dan, G A; Kalarus, Z; et al.
Abstract: Background: Anaemia is an independent predictor of atrial fibrillation (AF) and a common comorbidity. Real world data on the impact of anaemia on clinical outcomes, and on the benefits and risks of oral anticoagulation (OAC) are limited. Purpose: To investigate the association of different degrees of anaemia with adverse outcomes in a cohort of European patients with AF. Methods: We analyzed patients enrolled in the ESC-EHRA EORP-AF General Long-Term Registry with baseline hemoglobin (Hb) values. Patients were stratified according to World Health Organization (WHO) definition of anaemia: (i) No anaemia (Hb≥12.0g/dl for women and Hb≥13.0g/dl for men), Mild anaemia (Hb 11.0–11.9g/dl for women and Hb 11.0–12.9g/dl for men), and moderate-severe anaemia (Hb ≤10.9 g/dl for both sexes). Primary outcomes were all-cause death, major adverse cardiac events (MACE, as the composite of any thromboembolism (TE)/acute coronary syndrome/cardiovascular death) and major bleeding. Results: From the original 11, 096 AF patients enrolled in the Registry, 7767 (69.9%) were included in the present analysis (median age 70 years, interquartile range [IQR] 62–77, males 58.3%, CHA2DS2VASc score median 3 [2–4], HAS-BLED median 2 [1–2]). A total of 5973 (76.9%) patients did not have anaemia, 1156 (14.9%) had mild anaemia, and 638 (8.2%) had moderate/severe anaemia. Patients with anaemia were more likely to have more comorbidities, frailty, permanent AF and polypharmacy (≥5 drugs). Overall, 318 (18.4%) patients with anaemia and an indication for anticoagulation [i.e. CHA2DS2-VASc≥1 (males), or ≥2 (females)] did not receive any OAC. After a median (IQR) follow-up of 730 (692–749) days, all-cause death was 10.5% and there were 841 (11.6%) MACE and 186 (2.5%) major bleeds. Kaplan–Meier analysis showed a higher cumulative risk for patients with moderate-severe anaemia for all the outcomes considered (Figure) (Log Rank tests, all p<0.001). Adjusted Cox regression analyses revealed that patients with mild and moderate-severe anaemia had a higher risk for all-cause death (adjusted hazard ratio [aHR] 2.02, 95% confidence interval [CI] 1.71–2.40 and aHR 2.39, 95% CI 1.97–2.91, respectively), MACE (aHR 1.44, 95% CI 1.17–1.76 and aHR 1.64, 95% CI 1.30–2.07 respectively), and major bleeding (aHR 1.52, 05% CI 1.02–2.25 and aHR 3.73, 95% CI 2.59–5.37, respectively). Among patients with moderate-severe anaemia, use of OAC was associated with lower risk of all-cause mortality (HR 0.64, 95% CI 0.46–0.89) and MACE (HR 0.55, 95% CI 0.36–0.84), without a significant increased risk of major bleeding (HR 0.81, 95% CI 0.43–1.52). Conclusions: In a large contemporary cohort of European AF patients, almost 25% have concomitant anaemia which is associated with an increased risk for all-cause mortality, MACE and major bleeding. Use of OAC was associated with a lower risk of all-cause mortality in patients with moderate-severe anaemia, without significant increased risk of major bleeding. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Since the start of EORP, the following companies have supported the programme: Abbott Vascular Int. (2011–2021), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2021), Bayer (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and Pfizer Alliance (2011–2016), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2011–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2017), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2020), ResMed (2014–2016), Sanofi (2009–2011), SERVIER (2010–2021), and Vifor (2019–2022)